Application of GSN-based Security Argumentation Method in Product Functional Safety Assessment - XU Zhengjie; YIN Yuan; HUANG Aiping; TAN Qi; TAN Shaobo; CHEN Yao (Kongzhi Yu Xinxi Jishu)
The understanding of product safety acceptability by safety-related organizations mainly depends on whether the safety certification documents produced in the process of safety demonstration are comprehensive and accurate. Therefore, the goal structuring notation (GSN) method was used to construct a security demonstration model based on standard IEC 62425, combing the reasoning relationship between security objectives and security certification documents in the system life cycle, so as to effectively integrate the security evidence materials in security analysis, and a clear theory between security requirements and security evidence was established. Finally, the method was applied to the safety demonstration model of on-board balise equipment system, and good results were obtained.